Advancing urban adaptation where it counts: reshaping unequal knowledge and resource diffusion in networked Indonesian cities - and Geldin, Samuel (Environment and Urbanization, 2019)
Climate adaptation literature vocalizes the need for transnational municipal networks (TMNs) to expand activities in vulnerable medium-sized cities, but little work has examined the granular extent of city participation and processes constraining TMN growth. This study explores the effectiveness of TMNs in reaching adaptation outcomes and how financial, material, and knowledge exchanges of TMNs tend to exclude adaptation in high-priority intermediary cities. Nearly 40 semi-structured interviews with Indonesian city actors and a preliminary catalogue of cities participating in TMNs reveal that risk-averse selection criteria, insufficient impact assessments, and duplicative institutional efforts reinforce disparities between primary and intermediary cities. To effectively build adaptive capacity in the most vulnerable regions, TMNs should remove participation barriers for intermediary cities, improve incentives for institutional collaboration, and adopt more rigorous evaluative metrics. These results directly inform the governance, resource allocation, and operational goals of TMN stakeholders to advance distributive climate justice.